(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2008)
Pain and Quality of Life in Brazil: Nurses Perspectives ResumoA palestra, proferida durante o 3rd Congress of the World Union of Wound Healing Societies (WUWHS), trata de uma revisão bibliográfica acerca da produção científica de enfermeiros brasileiros sobre dor e qualidade de vida de pacientes em geral e, especificamente, de pacientes com feridas.Palavras Chaves: Qualidade de vida. Dor. AbstractThe article is a lecture presented at the 3rd Congress of the World Union of Wound Healing Societies (WUWHS) and refers to a bibliographic review about Brazilian nurses´ scientific production related to pain and quality of life in general and in wound care.Key words: Quality of life. Pain. IntroduçãoThe scientific production of Brazilian nurses on pain and quality of life (QOL), as wel as inter-related themes, is stil very incipient and the majority of studies found, are descriptive and cross-sectional, more diagnostic than related to tests of specific interventions, specialized or not. Studies on acute and chronic wounds are even scarcer.The purpose of this lecture, there is, the Brazilian nurses´ perspectives about patients´ pain and QOL led me to perform a bibliographic search in the thesis databases of two important institutions in the country - the University of Sao Paulo (www.usp.br/acervo.php) and the Coordination of Improvement of Higher Level Personnel - CAPES (www.capes.gov.br/servicos/bancodeteses.html). For this search, the period between 2004 and 2006 was included.Initialy, the search was performed through the folowing descriptors nursing AND pain AND quality of life, and 71 documents were obtained in the Dissertation database from USP. From these, 6 doctoral dissertations and 19 master theses refer to the theme proposed. The majority of these studies used qualitative methodology and was related much more to pain than to QOL itself.In addition to characterizing pain in different conditions (cancer, labor, fibromyalgia, surgeries, traumas, diabetic ulcer) including nursing diagnoses, and effects of some drugs, some critical studies on registration and systematization of pain assessment by nurses, perceptions and beliefs of health professionals regarding pain, and instruments or scales for evaluating pain were found, and finaly, only 6 studies on specific nursing interventions for the control of pain were verified.Among the studies searched, some results can be highlighted. They indicated that nurses do not keep many records regarding the patients’ pain, do not evaluate it in a systematized way, using or not objective instruments of evaluation or nursing diagnostics, and control the patients pain through pharmacological measures and not through those specific to nursing1-5. A quantitative study, using the Pain Attitude Inventory (PAI-short version) to know the beliefs of 75 health professionals, who work in 9 Centers of Chronic Pain in the city of Sao Paulo, presented some highly desirable and undesirable beliefs. The undesirable beliefs were related to medical cure and solicitude domains. The author concluded they can cause ambiguities, not only in the treatment but also in reinforcing unreal expectations, aggravating patients’ incapacities and dependency6.Hortense7 compared the perception of patients and professionals regarding several types of pain (nociceptive and neuropathic) through psychophysical methods. She observed that pain of oncological origin, in the myocardium infarct, renal colic, in burns and labor, were considered the most intense, in spite of the sample. However, there were divergences regarding perceptions on the intensity of some types of pain, among physicians and nurses compared to patients.Analyzing the 6 dissertations, in which specific nursing interventions were tested through clinical trials, both ample processes and more specific activities were found.In a randomized clinical trial with a 182 patients in post cardiac surgery, Silva8 studied the influence of the training process, assessment and systematized register of pain on the pain intensity, additional consumption of morphine, treatment of colateral effects, and satisfaction with analgesia. Results showed that training associated to the use of a systematic protocol improved pain control and patients satisfaction. Two studies in neonatology tested maternal contact9 and breastfeeding10 for pain relieve, respectively, in premature and new born babies, during blood colection for the PKU test. Both interventions showed effective for the pain control in children, in the two randomized clinical trials. Pain during and after labor was also subject of two other randomized clinical trials, in which the efficacy of the use of transcutaneous electrical nerve stimulation (TENS) for post Cesarean-section pain11 and post episiotomy pain in primiparas submitted to normal labor12. Despite reduced sample in both experimental and control groups, it evidenced positive pain control. In another investigation during labor, deambulation was evidenced as a worsening factor for pain, though was favorable for the other studied variables13.The CAPES database showed no documents when used the same descriptor indicating either absence of investigation related to both or inadequate use of descriptors.Using only quality of life as descriptor in both databases, 3242 documents were recovered, 88 of them developed by nurses. The majority was related to characterization of QOL in patients with different conditions, in addition to cultural adaptation and validation of instruments. Among the most studied groups, we found the oncological, elderly, cardiac, chronic renal diseases and respective treatments, pregnancy and menopauses.Twenty five articles of Brazilian nurses on pain and quality of life were found in the Latin American and Caribbean Literature in Health Sciences - LILACS (http://bases.bireme.br). Among the 25 articles found, only 11were considered for this analysis.Non-systematic bibliographic reviews predominated. They focused on back pain in pregnancy14, nursing interventions to the patient in pain15, influences on QOL of patients with chronic skin lesions16, headache17 and tumor wounds18. Characterization of pain in cancer19, and perceptions on pain in peripheral arterial disease with amputation20, with the use of opioids21 and of professionals who care of children and adolescents with cancer4(already mentioned) were also found. Only 3 studies focused on nursing interventions and 2 of them were related to therapeutic touch: a case study on pain relieve of multiple trauma patients22 and the other one, a controled clinical trial, focusing on patients with breast cancer in chemotherapy treatment, in which, pain was only one of the studied variables23. In the third publication, also a case study, the author evaluated the results of teaching-learning process of alternative methods for the pain control in spondylitis patients24.Analyzing teaching in nursing undergraduate programs from 37 Institutions of the Southeast region of Brazil, Bernardo25 verified that the majority (97.3%) informed to minister from 1 to a 130 class hours, with contents mainly related to pain concepts, types and assessment, with many deficiencies.Yet in the LILACS database, by using the descriptors nursing and quality of life, 366 publications presented thematic similar to those obtained in the dissertations databases, mainly related to the work of nursing students. The remaining referred to diabetic patients, patients with cancer, elderly, AIDS, cardiac, schizophrenic, and stoma patients. In their majority, they characterized patients´ QOL and a few focused on cultural adaptation and validation of instruments.As a few studies were repeated in the 3 databases, we concluded there are a reduced number of publications from academic production of post graduate nurses in addition to a delay in their publications, whether by factors related to the journals themselves, or by the students delay in forwarding finalized articles.Finaly, using three associated descriptors - nursing and quality of life and pain, in the Pubmed/Medline database, did not result in publications other than those already mentioned, whose journals are also indexed in these databases.Pain and QOL in wound careSpecificaly focusing on the main interest of this event, wound care, a few studies focused simultaneously on pain and quality of life of patients in these conditions, whether on the perception of the patients themselves or that of nurses and other health professionals.Among 2697 publications, searched through the descriptors pain and wound, 4 studies have been developed by Brazilian authors and only 1 of them by nurses. This was related to the adaptation of Burns Specific Pain Anxiety Scale26. When other descriptors were used, in which quality of life or pain was associated to the types of chronic lesions - venous, pressure and diabetic ulcers - even 176 studies were found, from which only one was identified as being carried out by us. It wil be presented later.Despite the scarcity of studies indexed in more known bases, I decided to present our studies on pain and QOL of patients with chronic wounds carried out in the last ten years. They are already published or are in press in specialized journals.In 2003, we published our first study, descriptive and cross-sectional, carried out with 20 adult patients, hospitalized with pressure ulcers in 3 hospitals in different cities. Its objective was to characterize pressure ulcer pain related. After agreeing in participate in the study, they were interviewed using a pain intensity numerical rating scale (10 points) and the short version of McGil Pain Questionnaire, adapted to Brazil. Qualitative pain assessment showed no typical time for the occurrence of pain that was most frequently experienced at rest and was constant in eighty percent of the patients. Moving in bed and sitting were compromised to a greater or lesser extent in 87.5% of the individuals, respectively. Average intensity of pain was moderate. The McGill Questionnaire showed that sensitive descriptive elements and burning were most frequently used to describe pressure ulcer pain. In addition, pain was also characterized as throbbing and tugging (sensitive descriptors) and unbearable (evaluative descriptor) in 25% of cases. Significant associations were observed. Black and Asian patients mentioned pain during movements and their pain impaired their appetites when compared to Caucasian patients; people with 2 or more ulcers presented pain at a typical time of the day when compared to those having single pressure ulcers and older patients mentioned impaired walking due to pressure ulcer pain27.Two years later, we published a study with similar objective and methods, this time to characterize chronic leg ulcers of a convenience sample of 90 outpatients, in 4 specialized services of two Brazilian cities. Eighty two percent of the patients had venous ulcers. Only 3 of the patients reported absence of pain related to leg lesions. All venous ulcers patients reported pain in their ulcers. The mean pain intensity of the "worst pain of the week" was moderate to severe. Twenty of the 30 McGil Questionnaire descriptors showed a choice frequency higher than 30%. Sensitive descriptors were the most frequently chosen by the patients to describe pain, like throbbing, driling, burning and stabbing. Lowest income patients and women reported the most intense pain and these data were correlated with alterations in sleep, movement, walking, and mood. Despite the presence of pain, 20% of the patients did not receive any medication for pain control. Non-pharmacological practices were also reported and included phytotherapy, resting, repositioning legs, massage, and dressings, as specific nursing care interventions28.In both studies, we sought to characterize pain, both qualitative and quantitatively, in some kinds of chronic wounds, inexistent in the country at the time. Although, it is essential the availability of instruments to assess pain, adapted and validated to our culture, it is even more important to have studies that indicate, in our field, the most frequent descriptors, specific to each type of pain, favoring diagnosis and more adequate specific interventions, also adapted to the demands of our clientele.QOL, as pain, has started to be studied in the health area only recently. Its publications are even more restricted or originate from academic studies, that is, with little application to the clinical practice of health professionals in general.To specificaly identify the impact of pain on QOL of 40 outpatients with chronic venous ulcers, we developed a cross-sectional study in São Paulo. Patients were assessed after undergoing ulcer cleansing. All the instruments were previously adapted for the Brazilian culture. Moderate pain was the most prevalent. Once again, sensory-discriminative pain descriptors were predominant. There were differences in percentage of words chosen according to level of pain (p<0.05). Sixteen of the 30 descriptors were chosen by more than 30% of patients and the most frequent pricking, sharp, sickening and troublesome, according to the domain. The pain management index (subtracting the pain level from the analgesic level) indicated inadequate analgesia. Compared with a no-pain group, those with pain presented lower overal QOL. Pain remained as predictor of overal QOL and of social QOL29.Despite differences between types of chronic ulcers of patients who composed the sample of the presented studies, some pain characteristics are similar. Regarding intensity, it varied from moderate to intense or severe, highlighting the venous ulcers. Sensitive descriptors or sensory-discriminant predominated and among the most common we had throbbing and burning.Among the affective domain the most cited were nagging and tiring and troublesome among the evaluative.Specificaly related to QOL, 89 adult patients with venous ulcers were interviewed using the generic version of the Ferrans & Powers Quality of Life Index (FPQLI), adapted for Brazilian culture. Scores range from zero - poor QOL - to 30 - the best QOL, with no cut-off established by the authors. The results showed that 37 patients presented a very good QOL and 35 a good QOL. The total QOL mean score was 22.3 and the domains scores ranged from 21 to 26.2, highest for Family domain. The item pain obtained one of the lowest mean scores, suggesting greater dissatisfaction of the patients with it. There were significant correlation between the psychological/spiritual subscale and the number of ulcers and between the family subscale. Patients who used to work on orthostatic position prior to the first VU showed significant better QOL for the HF and Fa dimensions30.The use of generic instruments for QOL assessment of people with wounds and the absence of a specific instrument that could be applied to patients with any kind of wounds, especialy chronic ones, led us to develop the Ferrans and Powers Quality of Life Index-Wound Version31.Since we had good experience with the use of generic version of Ferrans & Powers QLI in several studies with general population and specific group we decided to develop its wound version after Dr. Carol Ferrans´ consent. The instrument was developed based on the theoretical, empirical and analytical poles, according to proposed and published by Pasquali, in 1998. The theoretical pole included selection and analysis of the specific items and was based on a literature review and clinical expertise of the authors. The 8 specific wound items that were included in the original generic instrument are showed on the screen. Al of them were included on the Health and Functioning domain. This phase also included the analysis of the specific instrument content validity and semantics consecutively by a committee of experts and a patients´ focus group31.The empirical pole included the application of the version obtained at the end of the previous phases, to 362 wound outpatients from 16 health facilities, in 3 Brazilian states. And, finally, the analytical pole included the statistical strategies to analyze the psychometric properties of the QLI-WV. After submitting the data to these procedures, we obtained Cronbach´s alpha coefficients from 0.55 to 0.90 for overall QOL and domains, confirming the instrument internal consistency. Confirmatory Factor Analysis was also performed and showed that QLI-WV model was quite wel adjusted to the original one. Instrument stability was also confirmed by intra-class correlation coefficient very close to 1.0. Criterion concurrent validity was also confirmed through the significant positive correlations, moderate to strong, obtained between life satisfaction in general and the subscales, as wel as the total QLI-WV. The statistically significant positive correlation among QLI-WV subscales and most of the WHOQOL-brief subscales and also the strong correlation between the overal QOL scores for both instruments confirmed the convergent validity of this wound version. Finaly significant correlation with number and durability of wounds, age and pain confirmed its discriminant validity. These results allowed the authors to conclude that the QLI-WV is reliable and valid for patients with wounds of any type of etiology, except of cancer, AIDS and burns, in whose patients it was not applied31. After had been presented in some international conferences, at this time, the first procedures for its cultural adaptation in Spain are have just concluded in a post doctoral program of one of the authors. Next year it wil be probably adapted and validated for English culture, in USA, Canada or United Kingdom, in another post doctoral research scholarship.ConclusionIn conclusion and despite my first statement regarding the incipient scientific production of Brazilian nurses on pain and quality of life, advances have been reached. Teaching and research were found, in some nursing undergraduate and post graduate programs in the country, though, stil very concentrated in the most rich and developed regions of Brazil, such as Sao Paulo and Rio de Janeiro. In the wound area, on the other hand, there are eight nursing specializing courses in WOC care as wel as one nursing dermatological course, in addition to undergraduate courses, master and doctorate programs in these specialized areas. These education programs have permitted a higher academic and clinical development, with the inclusion of assessment instruments, whether of pain or QOL, in some care protocols, in some public and private institutions, pointing to perspectives more tuned to the international reality.